PENGARUH EFIKASI DIRI GURU DAN KOMITMEN MENGAJAR GURU ADMINISTRASI PERKANTORAN TERHADAP HASIL BELAJAR SISWA DI SMKN 1 KOTAMOBAGU - Dame, Joubert; Lempas, Jety; Rayo, Dirga Ayu Minggu (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2025)
This study aims to analyze the influence of teacher self-efficacy and teaching commitment on the learning outcomes of Office Administration students at SMK Negeri 1 Kotamobagu. Teacher self-efficacy is a teacher's belief in his/her ability to teach, while teaching commitment reflects the level of dedication and loyalty of teachers to their profession. This study uses a quantitative method with a survey approach. The research sample was class X Office Administration students selected through saturated sampling techniques. Data collection was carried out through questionnaires that had been tested for validity and reliability. The results of the regression analysis showed that teacher self-efficacy and teacher teaching commitment had a positive and significant effect on student learning outcomes, both partially and simultaneously. This finding confirms that the higher the teacher's self-efficacy and teaching commitment, the better the student learning outcomes. Therefore, it is recommended for schools to improve training and motivation programs for teachers in order to improve their self-efficacy and commitment to teaching. Keywords: Teacher self-efficacy, Office Administration, Teaching commitment, Learning outcomes